Neoliberal Policy and Equity on Campus: A Comparative Administrative Study of Name, Image, and Likeness (NIL) and College Athletics - Darrell Lovell (Journal of Social Equity and Public Administration)
This research analyzes NIL policy to determine its fit within the neoliberal policy framework and assesses its intersection with equity. Systemic and administrative factors within college athletics contribute to the NIL landscape. Disparities in earning potential are a natural product of market-based policies. Earnings and valuations by race and gender show equity ramifications. A comparative analysis of NIL policies and university websites and interviews shows a shift toward the neoliberal approach, providing targeted administrative mandates while promoting market capitalism within college athletics. As a result, NIL policy’s neoliberal tendencies have a significant impact on social equity.